GJB2 Mutations Linked to Hearing Loss Exhibit Differential Trafficking and Functional Defects as Revealed in Cochlear-Relevant Cells - Beach, Rianne; Abitbol, Julia M.; Allman, Brian L.; Esseltine, Jessica L.; Shao, Qing; Laird, Dale W. (Frontiers in Cell and Developmental Biology, 2020)
GJB2 gene (that encodes Cx26) mutations are causal of hearing loss highlighting the importance of Cx26-based channel signaling amongst the supporting cells in the organ of Corti. While the majority of these GJB2 mutations are inherited in an autosomal recessive manner, others are inherited in an autosomal dominant manner and lead to syndromic hearing loss as well as skin diseases. To assess if common or divergent mechanisms are at the root of GJB2-linked hearing loss, we expressed several mutants in cochlear-relevant HEI-OC1 cells derived from the developing organ of Corti. Since supporting cells of the mature mammalian organ of Corti have negligible Cx43, but HEI-OC1 cells are rich in Cx43, we first used CRISPR-Cas9 to ablate endogenous Cx43, thus establishing a connexin-deficient platform for controlled reintroduction of hearing-relevant connexins and Cx26 mutants. We found three distinct outcomes and cellular phenotypes when hearing loss-linked Cx26 mutants were expressed in cochlear-relevant cells. The dominant syndromic Cx26 mutant N54K had trafficking defects and did not fully prevent wild-type Cx26 gap junction plaque formation but surprisingly formed gap junctions when co-expressed with Cx30. In contrast, the dominant syndromic S183F mutant formed gap junctions incapable of transferring dye and, as expected, co-localized in the same gap junctions as wild-type Cx26 and Cx30, but also gained the capacity to intermix with Cx43 within gap junctions. Both recessive non-syndromic Cx26 mutants (R32H and R184P) were retained in intracellular vesicles including early endosomes and did not co-localize with Cx30. As might be predicted, none of the Cx26 mutants prevented Cx43 gap junction plaque formation in Cx43-rich HEI-OC1 cells while Cx43-ablation had little effect on the expression of reference genes linked to auditory cell differentiation. We conclude from our studies in cochlear-relevant cells that the selected Cx26 mutants likely evoke hearing loss via three unique connexin defects that are independent of Cx43 status.